2022
DOI: 10.1002/bse.3195
|View full text |Cite
|
Sign up to set email alerts
|

The link between sustainable business models and Blockchain: A multiple case study approach

Abstract: The paper investigates the relationship between Blockchain technology and new sustainable business models (SBMs). The literature notes a lack of empirical classifications and successful case studies. Using a multiple case studies methodology, our research article aims to answer the research question (RQ): How can Blockchain enable new SBMs and support the United Nations Sustainable Development Goals (SDGs)? We present 20 business stories extracted from a combined analysis of the databases coinmarketcap.com and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 78 publications
1
28
0
Order By: Relevance
“…Moreover, as Calandra et al (2022) recently suggested, a single case study is a suitable methodology for performing an in-depth analysis of relevant experiences. This methodology, indeed, allows scholars to obtain in-depth and robust understandings of an evolving phenomenon, such as the adoption of blockchain for social good.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, as Calandra et al (2022) recently suggested, a single case study is a suitable methodology for performing an in-depth analysis of relevant experiences. This methodology, indeed, allows scholars to obtain in-depth and robust understandings of an evolving phenomenon, such as the adoption of blockchain for social good.…”
Section: Methodsmentioning
confidence: 99%
“…However, a venture may implement more than one peculiarity of blockchain to solve one or more than one social objective. For instance, as also explained byCalandra et al (2022), the reliability, transparency, and decentralization peculiarities of blockchain allow a venture to solve several social objectives. A venture may implement these peculiarities to solve the SDG number 7 (Ensure access to affordable, reliable, sustainable, and modern energy for all) and SDG number 12 (Responsible consumption and production).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In this vein, the recovered food waste can be applied for human consumption, creating energy, producing bio‐based substances and extracting valuable compounds such as proteins and fats (Magnacca et al, 2020; Rajeh et al, 2021; Sadraei, 2020). On the other hand, food waste management has also been considered an important sustainability objective by the United Nations 2030 Agenda (Calandra et al, 2022; Pizzi et al, 2020; Santagata et al, 2021). Through the implementation of the Sustainable Development Goals (SDGs), food waste has been considered as related to specific goals such as goal number 2 named zero hungry (Goggins, 2018; Karki et al, 2021), number 12 on responsible consumption and production or number 17 on public‐private partnerships (de Visser‐Amundson, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…be applied for human consumption, creating energy, producing biobased substances and extracting valuable compounds such as proteins and fats (Magnacca et al, 2020;Rajeh et al, 2021;Sadraei, 2020). On the other hand, food waste management has also been considered an important sustainability objective by the United Nations 2030 Agenda (Calandra et al, 2022;Pizzi et al, 2020;Santagata et al, 2021).…”
mentioning
confidence: 99%